Studying the Disease Resistance and Morphological Variations in Cassava - Vidya, P.; Nair, Aswathy G.H.; Mohan, C.; Vijayan, Ambu; Sreekumar, J. (International Journal of Bio-resource and Stress Management, 2019)
Cassava is one of the most important tropical root crops with highest carbohydrate content feeding more than 800 million people all over the world. Cassava mosaic disease (CMD) is a geminiviral disease which causes serious yield penalties in cassava production in tropical and sub-tropical regions. The most reliable and long lasting mechanism to combat CMD is to utilize host plant resistance especially through R-gene mediated resistance. The present study aimed to identify polymorphism between cassava cultivars viz., MNga-1 and CI-732 using resistant gene candidates (RGC) degenerate primers. This study utilized eight degenerate primers (L6, I, RPS2, RPS5, RPP5, Xa-1, N, RGC2) to detect polymorphism and were observed between cassava cultivars amplified with primer pairs (I, RPS2, RPS5, RPP5). A total of 60 single nucleotide polymorphisms (SNPs) were observed between two cassava cultivars which included 21 transitions and 39 transversions. The identified polymorphism was used to synthesize cleaved amplified polymorphic sequences (CAPS) marker computationally using CAPS designer tool of SOL GENOME NETWORK and identified three CAPS markers in susceptible cultivar amplified with RPP5. These cultivars were selected as male and female parent in CMD resistant breeding studies. True hybrid evaluations of the F1 mapping populations were carried out using single allelic markers. Morphological characterizations of F1 mapping population were carried out based on cassava descriptors mentioned by IITA, Nigeria and were grouped using cluster analysis. It was also found that more than half of the F1 progenies (65) acquired morphological characters from female parent indicating the influence of female parent.